PROJECT ESTIMATION OF CORPORATE IDENTITY, PUBLIC CHARACTERISTICS AND PUBLIC PERCEPTION TOWARD THE HOTEL WEBSITE AT FIVE STARS HOTEL IN JAKARTA - Wibowo, Wihartantyo Ari; Prasetyawati, Dea (Academic Research Centre Services, 2014)
PROJECT ESTIMATION